Hibriditas Identitas Budaya Wayang Pada Film Made In Bali Karya Johar Prayudhi - Sandi, Kadek; Hikmah Purnama, Dadang (Jurnal Empirika, 2025)
This research reviews the Hybrid of Wayang Cultural Identity in the Movie Made in Bali, Work of Art by Johar Prayudhi, by observing the cultural transformation of Balinese wayang as a mixture of two cultures (Balinese and Japanese). The main artist is Made, a young player inheriting ancient tradition before the dilemma of defending traditional values versus accepting other cultural influences presented by Niluh, a friend of his with mixed Balinese and Japanese blood. This movie represents the negotiation process of cultural identity within the context of modernization and globalization. This research uses a qualitative approach through descriptive method as well as a visual ethnographic strategy. Analysis is based on the theory of Hybrid Homi K. Bhabha covering the Ambivalent concept, Mimicry, Third Space, and Metonymy of Presence. The outcome demonstrates that the Balinese wayang is not illustrated as traditional art, but also as a dynamic hybrid medium, so as to allow new identity formation through cultural exchange interaction. Hence, Made In Bali demonstrates that cultural identity is liquid, contextual, and negotiable. This research presents a contribution to the local cultural reviews through creative innovation in the globalization era.